An innovative double-flash binary cogeneration cooling and power (CCP) system: Thermodynamic evaluation and multi-objective optimization. (1st January 2021) - Cao, Yan; Mihardjo, Leonardus WW.; Dahari, Mahidzal; Ghaebi, Hadi; Parikhani, Towhid; Mohamed, Abdeliazim Mustafa
Abstract: In the present study an innovative double-flash binary geothermal (DFBG) system integrated with ejector cooling cycle (ECC) is devised for the cogeneration cooling and power purpose. The feasibility of the proposed cogeneration system is evaluated using exergy and thermal balance relations as the utmost productive tools. A comprehensive parametric evaluation is conducted, and it is found that the thermal and energetic performances of the unit can be maximized with adjusting separator 2 pressure. An accord with the performed parametric evaluation, it is discerned that the thermal efficiency of the devised electricity/cooling system can be enhanced with the booster pressure ratio and evaporator temperature. Furthermore, the results demonstrated that the exergy efficiency improves with reducing the booster pressure ratio, condenser pressure, and evaporator temperature or rising separator 1 pressure. Later, the productivity of the suggested set-up is optimized by highlighting energy and exergy efficiencies. Considering energy and exergy efficiencies simultaneously in an optimization mode, it is found that the net generated electricity and exergy efficiency can be improved by 62.33% and 57.78%, respectively. In addition, the results indicated that the highest exergy destruction rate is related to the condenser by the value of 3425 kW. Highlights: A novel combined cooling and power cycle is presented. Proposed cycle is assessed based on the first and second laws of thermodynamics. Proposed cycle is optimized using genetic algorithm. Comprehensive parametric analysis of key parameters of the new CCP cycle is performed.